"Malteški vitez" v mariborskem muzeju - Vrišer, Sergej (Studia Historica Slovenica, 2001)
The treatise is devoted to the thus far undefined portrait of a Maltese knight from the XVIII century in the Maribor Museum. Archival and art-history investigations brought about the finding that it is a portrait of Ferdinand von Hompesch, the last grand master in Malta, who ruled during 1798/99. The picture is evidently the work of an anonymous artist of the Maltese school at the end of the XVIII century
Keywords: cultural history; knights; kulturna zgodovina; Maribor; museums; muzeji; vitezi; Von Hompresch, Ferdinand